2021
DOI: 10.1111/nmo.14185
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing clinical features and location‐specific gene expression profiles associated with pain burden in children with functional dyspepsia

Abstract: Background In children with functional dyspepsia (FD), genes involved in pain modulation may be differentially expressed contributing to chronic pain. Methods Children with suspected FD (cases) and known eosinophilic esophagitis (controls) undergoing esophagogastroduodenoscopy completed the Rome IV Diagnostic, Pain Burden and Frequency Severity‐Duration questionnaires. Two antral and two duodenal biopsies were collected and relative fold differences in gene expression for 84 pain‐associated genes compared to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Prostaglandin, produced in a COX2-dependent manner, could act on the epithelium to regulate intravasation and immune cell function in malignant cells [16,17]. Previous studies have revealed that PTGES3 participates in the regulation of various diseases, including pediatric recurrent abdominal pain, oscillatory shear stress, dyspepsia, and cancers [18][19][20]. In recent years, there has been an increasing interest in the tumorigenic role of PTGES3 in multiple cancer types, including colorectal cancer, prostate cancer, and acute lymphoblastic leukemia [8,22].…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin, produced in a COX2-dependent manner, could act on the epithelium to regulate intravasation and immune cell function in malignant cells [16,17]. Previous studies have revealed that PTGES3 participates in the regulation of various diseases, including pediatric recurrent abdominal pain, oscillatory shear stress, dyspepsia, and cancers [18][19][20]. In recent years, there has been an increasing interest in the tumorigenic role of PTGES3 in multiple cancer types, including colorectal cancer, prostate cancer, and acute lymphoblastic leukemia [8,22].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, additional cochaperones are also known to interact with some of those listed. For example, the GR is one of the most widely studied Hsp90 clients, and changes in activity of GR and/or other clients due to altered abundance of associated cochaperones has been linked to mood disorders, autism, anxiety, psychotic illness, depression, and altered pain susceptibility ( Sinclair et al, 2013 ; Patel et al, 2016 ; Baker et al, 2018 ; Lee et al, 2019 ; Lou et al, 2021 ; Mokha et al, 2021 ; Salhi et al, 2021 ; Szczepankiewicz et al, 2021 ). Similarly, androgen receptor activity is highly dependent on cochaperones encoded by FKBP4, FKBPL, and SGTA ( Paul et al, 2014 ; Ilaslan et al, 2020 ; Sengun et al, 2021 ).…”
Section: Hsp90-cochaperone-client Interactions Relevant To Human Disordersmentioning
confidence: 99%
“…However, as analysed in a recent systematic review [24], no consistent association was found between most of the reported gene polymorphisms and FD. Moreover, a recent gene expression profiling study, conducted on duodenal biopsies of children, identified three candidate genes associated with FD pain [25]. Given the lack of major measurable molecular changes in FD, these patients represented a good control for our study.…”
Section: Introductionmentioning
confidence: 99%